2014
DOI: 10.1097/bot.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Displaced Intraarticular Calcaneal Fractures

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 59 publications
2
73
0
5
Order By: Relevance
“…This result agrees with the study published by Tornetta [49] that reported good clinical outcomes with PS only in patients with tongue fractures. The prognostic value of today’s most frequently used Sanders classification [50] has been recently validated by the same author comparing long-term clinical results [48]. That study was confirmed by ours; each considered variable obtained better values in the Sanders II group, and statistical analysis showed significantly lower AOFAS, MFS, PCS, and VAS scores comparing Sanders IV and both of the other two classes ( p  < 0.05).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This result agrees with the study published by Tornetta [49] that reported good clinical outcomes with PS only in patients with tongue fractures. The prognostic value of today’s most frequently used Sanders classification [50] has been recently validated by the same author comparing long-term clinical results [48]. That study was confirmed by ours; each considered variable obtained better values in the Sanders II group, and statistical analysis showed significantly lower AOFAS, MFS, PCS, and VAS scores comparing Sanders IV and both of the other two classes ( p  < 0.05).…”
Section: Discussionsupporting
confidence: 70%
“…Screw removal was performed in 18 cases (51.4 %) due to the protrusion of their heads from the bone profile and the resulting discomfort when wearing shoes. Secondary arthrodesis was performed in 4 cases (4.6 %), a percentage lower than those reported in other series (Makki et al, 10.6 % [47]; De Boer et al, 20 % after PS and 33 % in ORIF [41]; Sanders et al, 28.7 % [48]). The low percentage is due to patients’ reluctance to undergo joint fusion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…9) basiert auf der Anzahl der Gelenkfragmente im breitesten Bereich der posterioren Facette, basierend auf der Darstellung in der koronaren Rekonstruktion in der Computertomografie (CT). Die Klassifikation ist auch prognostisch relevant, zum Beispiel hinsichtlich einer im Langzeitverlauf notwendigen subtalaren Arthrodese [5]. bei Polytrauma, komplexen offenen Frakturen), ▪ primäre subtalare Arthrodese.…”
Section: Sanders-klassifikationunclassified
“…Displaced intra-articular calcaneal fractures (DIACF) is usually made by vertical violence delivered to the foot [3]. After many years of studding, management of displaced intra-articular calcaneal fracture has remained unclear for orthopedic surgeons and there is controversy to choose the best methods of treatment such as plates, bone graft and void filler [4]. Wide range of post-operative complications and variety of outcomes cause this complexity.…”
Section: Introductionmentioning
confidence: 99%